Violence and hooliganism in sports circles – a prevention and opinion poll in a documentary titled "No to Violence" - Takerkart, Faycel (sports creativity, 2025)
Sport is a socio-cultural phenomenon organically intertwined with the system of social entities and structures. General sporting progress and advancement depend on the social, cultural, economic, and political factors of each country. Therefore, a scientific view of sport cannot be limited to the natural sciences, such as biomechanics and biochemistry, but must also draw upon the social sciences, especially when examining sport and its human aspects. Sport is a distinct form of human activity that finds expression only through individuals and groups, within a socio-psychological framework with all its requirements. Sport is often described as a safe outlet for aggressive impulses and conflicts arising from factors like frustration, despair, and failure that people experience in their daily lives and cannot avoid. Since success is not limited to scoring points and goals, but also includes simply performing a skill well, sport is a successful social remedy against the factors of failure and frustration, and a socially acceptable outlet for releasing pent-up emotions and frustrations. Thus, an individual's self-acceptance is linked to their acceptance within a group, team, or organization. This means that acceptance, as a social need, is connected to the nature of social situations and the cultural framework the individual has experienced. Therefore, creating a healthy and suitable group, such as a sports team, allows the individual to develop important and balanced concepts that shape a child's personality, such as their body image and their perception of movement. An individual's sense of belonging to the group is achieved through the following factors: - Fulfillment of their needs through the group or team - Their readiness to play a role as a member of the group or team - The individual's confidence that their concepts align with those of the group or team